A retroviral promoter is sufficient to convert proto-src to a transforming gene that is distinct from the src gene of Rous sarcoma virus. - Zhou, H (1990)
The src genes of four natural isolates of avian sarcoma viruses differ from cellular proto-src in two genetic substitutions: the promoter of the cellular gene is replaced by a retroviral counterpart, and at least six codons from the 3' terminus are replaced by retroviral or heterologous cell-derived elements. Since virus constructs with a complete proto-src coding region failed to transform avian cells but acquired transforming function by point mutations of various codons, it has been proposed that point mutation is sufficient to convert proto-src to a transforming gene. However, promoter substitution is sufficient to convert two other proto-onc genes, proto-ras and proto-myc, to retroviral transforming genes. In view of this, we have reexamined whether promoter substitution, point mutation, or both are necessary to convert proto-src into a retroviral transforming gene. It was found that a recombinant virus (RpSV), in which the src gene of Rous sarcoma virus (RSV) was replaced by the complete coding region of proto-src, transformed quail and chicken embryo cells. The oncogene of RpSV differs from the src gene of RSV in three genetic properties: (i) it is weaker--e.g., transformed cells are flatter; (ii) it is slower--e.g., focus formation takes 9 to 12 days compared to 4 days for RSV; and (iii) its host range is narrower than that of RSV--e.g., only subsets of heterogeneous embryo cells are transformed by RpSV even after weeks or months. Replacement of the proto-src 3' terminus of RpSV by that of src from RSV generates a recombinant virus (RpvSV) that equals RSV in transforming function. It is concluded that a retroviral promoter, naturally substituted via illegitimate recombination with retroviruses, is sufficient to convert at least three proto-onc genes, src, myc, and ras, to retroviral transforming genes.